2018
DOI: 10.1186/s12884-018-1664-x
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional survey of knowledge of obstetric danger signs among women in rural Madagascar

Abstract: BackgroundAntenatal care (ANC) has the potential to identify and manage obstetric complications, educate women about risks during pregnancy and promote skilled birth attendance during childbirth. The aim of this study was to assess women’s knowledge of obstetric danger signs and factors associated with this knowledge in Ambanja, Madagascar. It also sought to evaluate whether the participation in a mobile health (mHealth) project that aimed to provide comprehensive ANC to pregnant women in remote areas influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
53
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(85 citation statements)
references
References 18 publications
10
53
5
1
Order By: Relevance
“…The specific danger signs mentioned by women in our study are similar to those from other low-middle income settings. Vaginal bleeding in pregnancy was mentioned consistently in a number of studies reporting danger signs during pregnancy (Hailu and Berhe 2014, Maseresha, Woldemichael et al 2016, Bintabara, Mpembeni et al 2017, Salem, Lacour et al 2018, including in our study. Swelling of the hands, feet and hands was also identified among women in Ethiopia Berhe 2014, Maseresha, Woldemichael et al 2016) and headaches and dizziness identified in rural Madagascar (Salem, Lacour et al 2018).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The specific danger signs mentioned by women in our study are similar to those from other low-middle income settings. Vaginal bleeding in pregnancy was mentioned consistently in a number of studies reporting danger signs during pregnancy (Hailu and Berhe 2014, Maseresha, Woldemichael et al 2016, Bintabara, Mpembeni et al 2017, Salem, Lacour et al 2018, including in our study. Swelling of the hands, feet and hands was also identified among women in Ethiopia Berhe 2014, Maseresha, Woldemichael et al 2016) and headaches and dizziness identified in rural Madagascar (Salem, Lacour et al 2018).…”
Section: Discussionsupporting
confidence: 71%
“…Vaginal bleeding in pregnancy was mentioned consistently in a number of studies reporting danger signs during pregnancy (Hailu and Berhe 2014, Maseresha, Woldemichael et al 2016, Bintabara, Mpembeni et al 2017, Salem, Lacour et al 2018, including in our study. Swelling of the hands, feet and hands was also identified among women in Ethiopia Berhe 2014, Maseresha, Woldemichael et al 2016) and headaches and dizziness identified in rural Madagascar (Salem, Lacour et al 2018). Although not identified as a danger sign directly relating to maternal outcomes, a number of studies, including ours, identified reduced fetal movement as a danger sign (Hailu and Berhe 2014, Maseresha, Woldemichael et al 2016, Salem, Lacour et al 2018).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Moreover, knowledge was very low and did not correlate with presence at ANC (either of the woman or her partner). Low knowledge of danger signs among women was also reported in studies in Madagascar, Tanzania and Ethiopia and often indicates overall poor quality of antenatal care [33,38,48]. Assessment of knowledge of danger signs among men is rarely carried out within maternal health care research, although it is well known that they play a major role in the referral of pregnant women in case of emergencies.…”
Section: Discussionmentioning
confidence: 99%